An Overview of Methods in the Analysis of Dependent ordered catagorical Data: Assumptions and Implications - Hans Högberg; Elisabeth Svensson (Örebro University School of Business, 2008)
Subjective assessments of pain, quality of life, ability etc. measured by rating scales and questionnaires are common in clinical research. The resulting responses are categorical with an ordered structure and the statistical methods must take account of this type of data structure. In this paper we give an overview of methods for analysis of dependent ordered categorical data and a comparison of standard models and measures with nonparametric augmented rank measures proposed by Svensson. We focus on assumptions and issues behind model specifications and data as well as implications of the methods. First we summarise some fundamental models for categorical data and two main approaches for repeated ordinal data; marginal and cluster-specific models. We then describe models and measures for application in agreement studies and finally give a summary of the approach of Svensson. The paper concludes with a summary of important aspects.
Keywords: C14; 330; Dependent ordinal data; GEE; GLMM; Logit; modelling